An exhaustive experimental evaluation on the effects of using Jatropha biodiesel as an admixture in a DI diesel engine powered by waste plastic fuel - Rajan Kumar; Manoj Kumar Mishra; Manish Kumar Roy (International Journal of Sustainable Energy, 2023)
Incorporating jatropha biodiesel into discarded plastic oil and diesel on diesel engines and analysis of six fuel samples, three diesel types and two waste plastic diesel and jatropha biodiesel combinations. Following characterisation, a one-cylinder, DI diesel engine underwent comprehensive performance and emissions testing, involving spectroscopy. Addition of jatropha biodiesel led to reduced viscosity and density of the waste plastic-diesel blend, a 20% decrease in flash point, and 10% reductions in BSEC and BSFC, while lowering the engine's thermal efficiency by 5%. Jatropha biodiesel increased HC by 30%, reduced CO and NOx emissions by 20% and 5%. Both diesel and WPF20D60JB20 exhibited a of 36.45%, with BSEC values at full load of 9.91 and 9.84 MJ/kW-hr. WPF20D60JB20 demonstrated the best performance.